PEMBERIAN PAKAN BUATAN TERHADAP PERTUMBUHAN IKAN NILA GIFT (Oreochromis sp) YANG DIPELIHARA DALAM HAPPA - Elrifadah Elrifadah (EnviroScienteae, 2013)
This study aims to determine the growth of gift tilapia (Oreochromis sp) were maintained in Happa in ponds with artificial feeding. This study uses a Quasi-experimental research, which was conducted in Freshwater Fish Culture Hall Mandiangin for 2 months. Research results indicate the relative weight of the resulting growth is 293.48% and for relatively long growth is 79.41%. Test fish feed conversion value is 1.62 with a degree of efficiency of feed utilization was 61.81%. Results of water quality measurements for temperatures ranging between 28-31oC, the pH of the water ranged between 6.5-7 and brightness between 41-74 cm of water.